Implementasi Pendidikan Akhlak Berbahasa dalam Pembelajaran Bahasa dan Sastra Indonesia di SD/MI - Wirayudha Pramana Bhakti (Jurnal Hikmatuna, 2018)
Affective domain of language learning is not only character education which is general, but education of morality language which is based on Al Quran and Hadith. Language akhlak education needs to be implemented from an early age through language learning so that learners have akhlakul karimah. This paper discusses the implementation of moral education in accordance with Al Quran and Hadith in learning Indonesian language and literature in primary school. The goal is to show that there are moral values ​​that are in accordance with Al Quran and Hadith on learning Indonesian language and literature. Thus, the direction and objectives of learning Indonesian language and literature more clearly, especially in the affective domain. Language akhlak that is implemented, namely: 1) speak properly both substance and redaction; 2) effective, efficient, and communicative language; 3) language with a rational reason; 4) language that does not hurt the heart; 5) the use of language to respect others; 6) the use of language in accordance with applicable norms; and, 7) the Islamic rules of listening.